Utilization of Various Livestock Feces for the Content of Nitrogen, Phosphorus, and Potassium in Organic Fertilizers - Isnaini Fathin Latifah; Engkus Ainul Yakin (Jurnal Biologi Tropis, 2026)
The utilization of livestock manure as an organic fertilizer has gained increasing attention as a sustainable strategy to improve soil fertility, reduce dependence on chemical fertilizers, and support environmentally friendly agricultural production. Livestock feces contain essential nutrients that can enhance soil nutrient availability and contribute to improved crop growth. Therefore, optimizing the processing and application of livestock manure is important to maximize its agronomic value. This study aimed to evaluate the effects of different treatments (P1, P2, and P3) on macronutrient content, including Nitrogen (N), Phosphorus (P), Potassium (K), and pH values. The research was conducted using a Completely Randomized Design (CRD) consisting of three treatments with several replications. Data obtained from the experiment were analyzed using Analysis of Variance (ANOVA) to determine treatment effects, followed by Duncan’s Multiple Range Test (DMRT) at a 5% significance level to compare differences among treatment means. The results showed that the treatments significantly affected all observed parameters (p < 0.05). Treatment P2 consistently produced the highest macronutrient contents, with mean values of 1.28% for Nitrogen, 1.52% for Phosphorus, and 1.78% for Potassium. In addition, P2 resulted in the highest pH value (8.72), indicating a more favorable condition for nutrient availability. Conversely, treatment P3 exhibited the lowest values for both nutrient content and pH. Duncan’s test further confirmed that treatment P2 differed significantly from the other treatments and demonstrated superior performance across all measured variables. These findings indicate that treatment P2 is the most effective method for enhancing the quality of livestock manure-based organic fertilizer through improved macronutrient content and pH characteristics.